THE VALIDITY AND PRACTICALITY OF PHYSICS LEARNING MEDIA ON MEASUREMENT TOPIC USING GOOGLE SITES - Ramadani, Desi (Department of Physics Universitas Negeri Padang, 2025)
This research addresses the need for engaging and accessible physics learning media by developing and evaluating a Google Sites-based resource for the topic of Measurement, designed for tenth-grade students. This study employed a Research and Development (R&D) methodology, utilizing the ADDIE model, but was limited to the analysis, design, and development phases, which included comprehensive feasibility testing. The feasibility assessment involved two key stages: a validity test conducted by a panel of six experts (three UNP Physics lecturers and three senior Physics teachers from SMAN 5 Padang) , and a practicality test with end-users (three Physics teachers and 40 tenth-grade students at SMAN 5 Padang). Data were collected using validated questionnaires. The validity data were analyzed using Aiken's V statistic, while practicality data were analyzed using descriptive percentage analysis. The findings indicated a high level of validity, with an average Aiken's V score of 0.90. The practicality assessment also yielded positive results, with teachers awarding an average score of 93.6% (Very Practical), and students providing an average score of 84.21% (Very Practical). These results confirm that the developed Google Sites-based learning media is both valid and highly practical for implementation in the physics learning process.